λ-Statistical Convergence of Sequences of Functions in Intuitionistic Fuzzy Normed Spaces - Karakaya, Vatan; Simsek, Necip; Erturk, Muzeyyen; Gursoy, Faik (HINDAWI LTD, 2012)
We study lambda-statistically convergent sequences of functions in intuitionistic fuzzy normed spaces. We define concept of lambda-statistical pointwise convergence and lambda-statistical uniform convergence in intuitionistic fuzzy normed spaces and we give some basic properties of these concepts.